Wikipedia Community Health Dashboards - Denina, Andrea; Aliprandi, Paolo; Miquel-Ribé, Marc; Laniado, David; Consonni, Cristian (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
Wikipedia relies on the contributions of hundreds of thousands of volunteers across hundreds of language communities. The long-term health of Wikipedia's editor base is essential for the platform's stability and growth, and assessing it requires metrics that are reproducible, comparable over time, and regularly updated. Prior work introduced the Community Vital Signs, a set of six language-independent indicators capturing editor retention, stability, generational balance, role renewal, and global participation. In this paper, we present a live demonstration of the Wikipedia Community Health Dashboards, a set of interactive visualizations for exploring these indicators across all Wikipedia language editions. The dashboards are powered by a fully automated, open-source pipeline that updates the metrics monthly. We describe the system architecture and showcase how the dashboards enable researchers and community members to monitor and compare community health over time.